-4(u+1)=5u+5

Simple and best practice solution for -4(u+1)=5u+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(u+1)=5u+5 equation:


Simplifying
-4(u + 1) = 5u + 5

Reorder the terms:
-4(1 + u) = 5u + 5
(1 * -4 + u * -4) = 5u + 5
(-4 + -4u) = 5u + 5

Reorder the terms:
-4 + -4u = 5 + 5u

Solving
-4 + -4u = 5 + 5u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-5u' to each side of the equation.
-4 + -4u + -5u = 5 + 5u + -5u

Combine like terms: -4u + -5u = -9u
-4 + -9u = 5 + 5u + -5u

Combine like terms: 5u + -5u = 0
-4 + -9u = 5 + 0
-4 + -9u = 5

Add '4' to each side of the equation.
-4 + 4 + -9u = 5 + 4

Combine like terms: -4 + 4 = 0
0 + -9u = 5 + 4
-9u = 5 + 4

Combine like terms: 5 + 4 = 9
-9u = 9

Divide each side by '-9'.
u = -1

Simplifying
u = -1

See similar equations:

| X^2dy+y^2dx= | | (2x+4)+(4x+2)=(6x+6) | | 17=3u+2 | | -3x+92=4x+1 | | -11=-8+r-3 | | -12=5x+8x | | 6(-1-7k)=-8(7-k) | | 8(9-2k)=9(1-k) | | 8x+38=6x+6240 | | -11(8m-6)=-2-7(12m-8) | | -23+6x=5x+2(5x+2) | | 8p+21=-3(-8p-7) | | -11=8+r-3 | | (12x-8)+(12x-8)=(22x-11) | | 2(5+5k)=4+8k | | 1d/10-12 | | 3-1/t-2/t^2=0 | | lx-2l=2x+1 | | f(x)=7x^2+4x-3 | | 0.05x-0.1x+0.6=0.04x+2.22 | | (8x-3)+(8x-3)=(10x+30) | | =29*4 | | 7700+1900+700+160= | | 0.05x-0.1x+0.6=0.04+2.22 | | 0.05-0.1x+0.6=0.04+2.22 | | =(81+162t^2+81t^4) | | =sqrt(81+162t^2+81t^4) | | 4.25E-19= | | =32sin^2(t)cos^2(t) | | F=7/4(n-9) | | 1/2*3x*4x=216 | | (4x-5)(3x)= |

Equations solver categories